PERLUKAH BRANDING PADA SEKOLAH? STUDI KASUS PADA SMP SWASTA DI SURABAYA - Zulaikha, Zulaikha (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2017)
As a community-related institution directly, schools also have to create a brand for their institutions. The brand attached to the (positive) school institution will determine how its graduates are at higher school institutions and how their graduates are in the world, including in the world of work. Brand is also one of the determinants of the choice of students choose the school as a school that he chose, and make it has a favorite school predicate or not. The phenomenon that happened so far, the school has not been specifically build its brand. Nevertheless, it has been mapped in the minds of the public, which schools are favorites and which are not, word of mouth or word of mouth between students and parents. Word of mouth not only contains positive issues about the school, but also vulnerable to build a negative image and brand about the school in question. This research seeks to collect data on how the school sees its institutional branding, and what its efforts are in building its school branding. The results of this study indicate the media can not distinguish between brand building with media relaitons. Be aware of the brand, less. The three schools that became the object of research, the favorite Islamic Schools, favorite Christian schools and non-favorite private schools, show the same reality, there has been no awareness of branding.Keywords: brand, branding, school branding, media relations